TRADISI PERANG BANGKAT PADA MASYARAKAT SUKU OSING BANYUWANGI: PERSPEKTIF HUKUM ISLAM - Sugiyanto, Muhammad Nur Kharis (UIN Sunan Kalijaga Yogyakarta, 2017)
This paper examines the implementation of the marriage tradition of Perang Bangkat in Kemiren Banyuwangi, East Java, from the perspective of Islamic law. This tradition has sparked debate among Muslims. Some of them consider that the tradition of war has deviated from the teachings of Islam, while others think that it was not against the teachings of Islam. This paper explains that the tradition is a marriage ritual between a pair of brides with the status of a sonship (youngest) married to a fellow surname, the firstborn with the firstborn and the youngest child with the firstborn in each family. The hope of his household life will be happy. Implementation of this ritual was carried out before the marriage ceremony took place and was done at the time of afternoon, when the sun began to sink, around the time of maghrib arrived. This paper further confirms that this tradition is permissible in Islam because it includes community customs that are not contrary to the rules of Islamic law (al-'urf as-sahih). Thus, the law to perform the ritual tradition is allowed as long as it does not harm one party and there is no element that contradicts to the Islamic law